The tight junction protein TJP1 regulates the feeding-modulated hepatic circadian clock - Yi Liu (Nature Portfolio, 2020)
The circadian clock regulates rhythms of physiology and metabolism in response to environmental cues such as food intake. Here, the authors show that tight junction protein 1 (TJP1) interacts with period 1 and modulates its nuclear translocation in a mTOR-dependent manner.